Faktor-faktor yang mempengaruhi capital adequacy ratio pada bank listing di BEI periode 2010-2014 - Rizky Astreanto; Selamet Riyadi (Sekolah Pascasarjana Perbanas Jakarta, 2017)
The purpose of this study was to analyze the factors affecting the bank's Capital Adequacy Ratio listing on the Stock Exchange in 2010-2014, as well Analyzing Independent variables Return On Asset, loan to deposit ratio, Non Performing Loan, Equity Multiplier and the Size of the most dominant influence on the bank's Capital Adequacy Ratio listing on the Stock Exchange. the data used in this study is the monthly data from January 2010 to December 2014. this study uses panel data regression analysis. the results showed that the Return on Asset has no effect on Capital Adequacy Ratio, Loan to Deposit Ratio negatively affect the number of Capital Adequacy Ratio, Non Performing Loan significant negative effect on the Capital Adequacy Ratio, Equity Multiplier significant negative effect on Capital Adequacy Ratio and Size does not affect the Capital Adequacy Ratio. for further research may use additional independent variables such as external factors affecting the Bank's Capital Adequacy Ratio in Commercial and increase the range of years of research to produce new data every year.